Pauline theology ministry and society - Ellis, Edward Earle, 1926- (Grand Rapids, MI Eerdmans, 1989)
Includes bibliographical references and indexes
A revision and expansion of lectures delivered in the US, UK, Sth Africa and Ciskei
Keywords: Bible. N.T. Epistles of Paul -- theology; Clergy -- biblical teaching; Church -- biblical teaching; Holy Spirit -- biblical teaching; Gifts, spiritual -- biblical teaching; Woman (Christian theology) -- biblical teacing; Sociology, Biblical